Metabolism of stevioside by chickens - Geuns, JMC; Malheiros, R. D.; Moraes, VMB; Decuypere, EMP; Compernolle, F.; Buyse, J. G. (Amer Chemical Soc, 2003)
In intubation experiments (643-1168 mg per animal), most of the stevioside administered to chickens was recovered unchanged in the excreta, and only about 2% was converted into steviol. Neither stevioside nor steviol could be found in the blood. In chronic studies (667 mg of stevioside/kg of feed) with laying hens and meat-type chickens, no significant differences were found in feed uptake, weight gain, and feed conversion as the result of stevioside administration. The egg production and egg composition of laying hens were not influenced. Most of the stevioside taken up was found untransformed in the excreta, and about 21.5% or 7.3% was converted to steviol by meat-type chickens or laying hens, respectively. No stevioside or steviol could be detected in the blood or in the eggs of the different groups of animals. In anaerobic incubation experiments with chicken excreta, only a 20% conversion of stevioside into steviol was found. No harmful effects were observed in the chronic stevioside supplementation experiments nor in the intubation experiments in which very high stevioside doses were given.
Keywords: Stevia rebaudiana (Bertoni) Bertoni; stevioside; rebaudioside A; steviol; metabolism; chicken; Gallus gallus domesticus; toxicology